2002
DOI: 10.1038/sj.ejhg.5200760
|View full text |Cite
|
Sign up to set email alerts
|

Human chromosome 15q11-q14 regions of rearrangements contain clusters of LCR15 duplicons

Abstract: Six breakpoint regions for rearrangements of human chromosome 15q11-q14 have been described. These rearrangements involve deletions found in approximately 70% of Prader-Willi or Angelman's syndrome patients (PWS, AS), duplications detected in some cases of autism, triplications and inverted duplications. HERC2-containing (HEct domain and RCc1 domain protein 2) segmental duplications or duplicons are present at two of these breakpoints (BP2 and BP3) mainly associated with deletions. We show here that clusters c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 45 publications
4
106
0
1
Order By: Relevance
“…Strikingly, none of the 18 cases studied was found to contain the BAC 489D6 (marker D15S144) that marks the most distal boundary of BP5. 18 Indeed, our FISH studies demonstrated that five inv dup (15) had a breakpoint located within BP3 (Figure 1), three had a breakpoint located within BP4 and 10 had a breakpoint within BP5.…”
Section: Comparison Of Breakpoints Between the Translocations And Larmentioning
confidence: 99%
See 3 more Smart Citations
“…Strikingly, none of the 18 cases studied was found to contain the BAC 489D6 (marker D15S144) that marks the most distal boundary of BP5. 18 Indeed, our FISH studies demonstrated that five inv dup (15) had a breakpoint located within BP3 (Figure 1), three had a breakpoint located within BP4 and 10 had a breakpoint within BP5.…”
Section: Comparison Of Breakpoints Between the Translocations And Larmentioning
confidence: 99%
“…18 Using the Human Genome Segmental Duplication Database Assembly program, we found a LCR15-duplicon element located adjacent to the BAC 64O8, very close to the proximal boundary of the 460 kb interval (Figure 4). This LCR15-duplicon (sequence AC027139) extends through 270 kb and is present at all other BPs that characterize recurrent rearrangements of chr 15.…”
Section: Comparison Of Breakpoints Between the Translocations And Larmentioning
confidence: 99%
See 2 more Smart Citations
“…47 The BP1, BP2, and BP3 regions are characterized by low-copy repeat regions that contain repeats mainly derived from the ancestral HECT domain and RCc1 domain protein 2 genes (HERC2). 100 The BP sites distal to BP3 contain other low-copy repeat regions (e.g., without HERC2 duplications) that share chromosome 15-derived repeated DNA elements. A proportion of mothers who have a child with an AS deletion have been found to have inversions in the 15q11.2-q13 region (the region deleted in the offspring with AS).…”
Section: Deletions Of 15q112-q13 (65-75%)mentioning
confidence: 99%